In situ mechanical testing of hard yet tough high entropy nitride coatings deposited on compliant steel substrates - Kuczyk, Martin; Zawischa, Martin; Krülle, Tim; Vollhüter, Jan; Zeiler, Stefan; Leonhardt, Michael; Kaspar, Jörg; Zimmer, Otmar; Göken, Mathias; Leyens, Christoph; Zimmermann, Martina (Thin Solid Films, 2023)
High entropy nitrides are an interesting material class for wear resistant coatings. Their fracture properties and toughness are of particular interest for future application in tool coatings. Therefore, in situ tensile testing and micro-cantilever experiments were performed on (AlCrTaTiZr)N, (AlCrNbSiTiV)N, (HfNbTaTiVZr)N and (AlTi)N coatings inside a scanning electron microscope. Parallel cracks form during tensile testing from which the fracture toughness was determined via a modified Hsueh and Yanaka model. For this the misfit strain between coating and substrate was treated as an unknown parameter and was fitted to the beginning part of the underlying crack density – applied strain curves. The validity of the model was evaluated by comparing the results with fracture toughness values derived via micro-cantilever bending experiments. A good fit between the data could be observed for three out of four tested coatings. The limitations of the underlying analytical model are presented and discussed. The tested high entropy nitride coatings displayed a promising combination of high hardness and fracture toughness.
CRIS-Team Scopus Importer:2023-12-08
Keywords: Fracture toughness; High entropy nitrides; In situ mechanical testing; Micro-cantilever testing; Tensile testing